A checklist of polyclad flatworms (Platyhelminthes: Polycladida) from the Caribbean coast of Colombia, South America - Quiroga, Sigmer Y.; Bolaños, D. Marcela; Litvaitis, Marian K. (Zootaxa, 2004)
Although the Polycladida (Platyhelminthes) are prominent members of many reef communities, no comprehensive surveys exist for the Caribbean coast of Colombia. This study represents a first survey of the Colombian polyclad fauna. A total of 25 species were collected from the rocky littoral of the Tayrona National Park, Santa Marta, Colombia. Because color and color patterns represent major taxonomic characters in the classification of polyclads, photographic records were obtained from live specimens prior to fixation. Further taxonomic identification was based on major external features and serial longitudinal sections of the reproductive system. Numerically, Boninia divae Marcus and Marcus, 1968, followed by Styloplanocera fasciata (Schmarda, 1859) were the most abundant species. Not only do all recorded species constitute first records for the Colombian coast of the Caribbean, but Cestoplana rubrocincta (Grube, 1840), Armatoplana divae (Marcus, 1947), Phaenoplana longipenis (Hyman, 1953), Eurylepta aurantiaca Heath and McGregor, 1912, Thysanozoon cf. lagidum Marcus, 1949, and Prosthiostomum gilvum Marcus, 1950 represent first records for the entire Caribbean region. Furthermore, a new combination Phrikoceros mopsus nov. comb. is proposed, and a possible new species of Pleioplana Faubel, 1983 was found.